The role of survivin in autophagy - Humphry, Nicola (2018)
Survivin is a highly conserved protein with important roles in cell death and mitosis; deletion of the survivin gene is embryonically lethal. It is highly expressed in most cancers, making it a promising target for cancer therapy. Autophagy, an important homeostatic cellular recycling system, promotes cell survival under stresses such as DNA damage, nutrient starvation and hypoxia.